2010
DOI: 10.1002/pen.21746
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flexible linking of polyurethane copolymer and the effect on shape recovery and tensile mechanical properties

Abstract: Shape memory polyurethane (SMPU), flexibly crosslinked via a polyethyleneglycol (PEG) spacer attached to its side through an allophanate group, was tested for shape memory and compared with a linear SMPU. The new SMPU was composed of 4,4′‐methylenebis(phenylisocyanate) (MDI), poly(tetramethyleneglycol) (PTMG‐2000), and 1,4‐butanediol (BD), and included polyethyleneglycol (PEG‐200) as a spacer. A second MDI, linked to the carbamate group of the first MDI, served as the connecting point for the PEG‐200. Two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…The increase in the maximum stress for the UA and IUA series was due to the physical cross-linking of the grafted PA chains and the light chemical cross-linking of PU chains by MDI-3 (Scheme 1c), whereas the loss of PA chains in the C series was responsible for the low tensile stress. The maximum tensile stresses of the UA and IUA series were comparable to those of PUs with flexible cross-linking: the PEG cross-linked PU exhibited a maximum stress of 56 MPa [35], and the PDMS cross-linked PU showed a maximum stress of 53 MPa [23]. The breaking strain increased slightly for the UA series and remained the same for the IUA series with an increase in the PA content: the breaking strain changed from 1496 % for L to 1686 % for UA-1, 2024 % for UA-3, 1646 % for IUA-1, and 1633 % for IUA-3 (Fig.…”
Section: Tensile and Shape Memory Propertiesmentioning
confidence: 71%
“…The increase in the maximum stress for the UA and IUA series was due to the physical cross-linking of the grafted PA chains and the light chemical cross-linking of PU chains by MDI-3 (Scheme 1c), whereas the loss of PA chains in the C series was responsible for the low tensile stress. The maximum tensile stresses of the UA and IUA series were comparable to those of PUs with flexible cross-linking: the PEG cross-linked PU exhibited a maximum stress of 56 MPa [35], and the PDMS cross-linked PU showed a maximum stress of 53 MPa [23]. The breaking strain increased slightly for the UA series and remained the same for the IUA series with an increase in the PA content: the breaking strain changed from 1496 % for L to 1686 % for UA-1, 2024 % for UA-3, 1646 % for IUA-1, and 1633 % for IUA-3 (Fig.…”
Section: Tensile and Shape Memory Propertiesmentioning
confidence: 71%
“…The sharp increase in the maximum stress for the UP, UE, and UO series was due to the PVA cross-linking of the PU chains, whereas the free PVA chains in the Control series did not form the crosslinking, resulting in the decrease in tensile stress. The maximum tensile stresses of the UP, UE, and UO series were comparable to those of PUs with flexible cross-linking: the PEG cross-linked PU exhibited a maximum stress of 56 MPa [13], and the PDMS cross-linked PU showed a maximum stress of 53 MPa [14]. The breaking strain slightly increased for the UP, UE, and UO series and remained the same or decreased for the Control series with an increase in the PVA content: the breaking strain changed from 1496 % for L to 1686 % for UP-3, 2071 % for UE-3, 1783 % for UO-3, and 1635 % for CPU (Figure 7(b)).…”
Section: Tensile and Shape Memory Propertiesmentioning
confidence: 72%
“…PUs could be cross-linked using the terminal sites to improve the mechanical strength and thermal stability [11,12]. However, a lateral flexible crosslinking method was introduced to PUs to improve the tensile strength without a decrease in the strain [13,14]. The lateral linking of functional groups to PU side was well established and was applied to the functionalization of PU [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that the ECH cross-linking in the PU series did not reduce the tensile strain although the ECH crosslinking was expected to restrict the stretching of the PU chains. The tensile properties of the PU series were not inferior to those of PUs with flexible cross-linking: Polyethylene glycol (PEG) cross-linked PU exhibited a maximum stress of 56 MPa and strain at break of 1568% 14 and PDMS cross-linked PU showed a maximum stress of 53 MPa and strain at break of 1407%. 15 The tensile test results revealed that the ECH cross-linking in the PU series significantly improved the tensile strength without the decrease in tensile strain compared to the unmodified PU (L).…”
Section: Tensile and Shape Memory Propertiesmentioning
confidence: 89%
“…12,13 An advanced flexible cross-linking method was successfully tried to laterally link PUs using a flexible polyethylene glycol or a poly(dimethylsiloxane) spacer to improve the tensile strength without a decrease in the strain. 14,15 To laterally crosslink PUs, the PU side should be modified with functional groups to anchor the cross-linking agents. The PU modification method has already been applied to improve the biocompatibility, 16,17 Advances hydrophilicity, 18 pH sensitivity, 19 and antimicrobial activity 20 of the PU surface.…”
Section: Introduction Ementioning
confidence: 99%